2019
DOI: 10.4102/phcfm.v11i1.1914
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of attitudes, trends and perceptions of smoking among middle and secondary school students in the Gharb Region, Morocco, 2010–2015

Abstract: Background Tobacco use is an important public health issue. Morocco implemented a tobacco control programme, which has been ongoing among students at middle and secondary schools since 2010. Aim This study aims to compare the trend in smoking among the programme beneficiaries with the results of the initial study conducted prior to the implementation of the programme. Setting This study was conducted in middle and secondary schools of the Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…High rates of low SK were observed, especially about the effects on oral health and the second-hand effects, indicating possibilities for improvements. These findings agree with several previous studies that observed low levels of knowledge on the harms of smoking among adolescents using objective measurements [5][6][7][8][9][10][11][12][13][14] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High rates of low SK were observed, especially about the effects on oral health and the second-hand effects, indicating possibilities for improvements. These findings agree with several previous studies that observed low levels of knowledge on the harms of smoking among adolescents using objective measurements [5][6][7][8][9][10][11][12][13][14] .…”
Section: Discussionsupporting
confidence: 92%
“…Many adolescents may not be aware that smoking is harmful for their health [4][5][6][7][8][9] , especially regarding second-hand smoking [10][11][12][13] and oral health effects 14 . A lack of knowledge about the hazards of smoking has been described as a predictor of smoking status 13,[15][16][17][18] and susceptibility to smoking [19][20][21] in this population group.…”
Section: Introductionmentioning
confidence: 99%